Coining for Capital : Movies, Marketing, and the Transformation of Childhood - Kapur, Jyotsna (Book collections on Project MUSE., 2005)
""This book is a welcome addition to the literature on children and the media, and a most stimulating application of social theory to questions of the child in contemporary film and consumer culture.""-Ellen Seiter, author of The Internet Playground: Children's Access, Entertainment and Mis-Education Since the 1980's, a peculiar paradox has evolved in American film. Hollywood's children have grown up, and the adults are looking and behaving more and more like children. In popular films such as Harry Potter, Toy Story, Pocahantas, Home Alone, and Jumanji, it is the children who ar.